Expanding the footprint of the Storegga tsunami through new evidence from Arctic marine sediments - Dhanushka Devendra; Magdalena Łącka; Natalia Szymańska; Hasitha Nethupul; Joanna Pawłowska; Małgorzata Szymczak-Żyła; Magdalena Krajewska; Prasadi De Silva; Stein Bondevik; Steven J. Gibbons; Marek Zajączkowski (Scientific Reports)
Abstract The Storegga tsunami, dated to 8150 years ago, disturbed sea floor sediments near its source. Here, we present evidence that sediments as far north as the Kveitehola Trough (75° N) in the NW Barents Sea were affected by the Storegga tsunami. We identified an 18-cm-thick sandy mud unit, characterized by coarser grains at its lower boundary, to be deposited between 8100 and 8600 years BP. The unit contained significantly older foraminiferal tests, radiocarbon dated to between 12,000 and 27,000 years BP, that have been interpreted to be redeposited. In addition, the unit shows elevated signals of terrestrial plant sequences (sedaDNA) and terrestrial steroids. Simulation of the Storegga tsunami reveals strong currents in the shallower parts of the Barents Sea that were capable of moving sediments on the sea floor. We suggest that the tsunami backwash from the inundation of northernmost Norway or Bjørnøya could have carried terrestrial signals to the sediment core location.